Đặc trưng từ vựng tiếng Nhật (nhìn từ thực trạng giảng dạy môn từ vựng học tại khoa tiếng Nhật, Trường Đại học Hà Nội) /Nguyễn Thị Đặng Thu. - Nguyễn, Thị Đặng Thu.
“Word” has unanimously been regarded as one of the most basic linguistic units. In many researches on any language, linguists have usually raised the issue of how to define this linguistic unit. But this is an unsolvable problem because in general linguistic studies “word” is not a univalent notion. It is defined differently in different languages, even within one and the same language. This explains why debates and discussions on the notion of “word” in linguistic studies have not had any endings and perhaps will have no endings. In this aricle, the authors provided an overview of how scholars have conceptualized and defined the notion of “word” in languages, explained why it is difficult to solve this unsolvable problem, and offer some methodological solutions to this problem.